1999
DOI: 10.1111/j.1447-0756.1999.tb01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Leiomyoma in Pregnancy: Its Influence on Obstetric Performance

Abstract: Although pain in the lower abdomen, the requirement of tocolytic treatment, preterm delivery, and cesarean delivery were common, the neonatal outcome was fairly good in women with uterine leiomyomas. The present data might be encouraging to pregnant women with uterine leiomyomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2
15

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 6 publications
3
30
2
15
Order By: Relevance
“…(15/136), similar to that previously reported by other authors (10)(11)(12)(13). Our data also confirms that the rate of fetal growth restriction in pregnancies is not increased in pregnancies complicated with fibroids.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 92%
See 2 more Smart Citations
“…(15/136), similar to that previously reported by other authors (10)(11)(12)(13). Our data also confirms that the rate of fetal growth restriction in pregnancies is not increased in pregnancies complicated with fibroids.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 92%
“…However, our findings did not show a relationship between mode of delivery and the number of fibroids, which conflicts with previously reported findings 7,11 . Although some studies 12,14 suggested that larger fibroids were more likely to be associated with operative delivery, we could not demonstrate a similar association. In fact, our data support the conclusions of a study by Roberts et al 15 where multiple or larger fibroids were not associated with increased risk of caesarean section.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 86%
See 1 more Smart Citation
“…The risk factors are shown in Table 1, and experimental results are consistent with the reported literature [13][14][15][16]. Blood clotting function tests include fibrinogen (FIB), plasma prothrombin time detection (PPTD) and so on [17][18][19][20]. In the PPH group in the current study, 103 parturient patients presented placental factors, with a morbidity rate of 23%.…”
Section: Discussionsupporting
confidence: 87%
“…Fibroids are linked with both malpresenation 17 and preterm labor, 18 probably by distorting the uterine cavity. Our study identified 2 of 33 (6.1%) malpresentations, and 1 face presentation, a rate that is not increased.…”
Section: Commentmentioning
confidence: 99%